Les sites pornographiques par le menu : pornotypes linguistiques et procédés médiatiques - François Perea (Genre, Sexualité et Société)
This paper analyses the navigation menus of heterosexual pornography websites, which are organised in “Categories”, designed to classify video extracts and guide the user. The analysis of these categories (the characters, their sexual activities and the media processes) leads us to propose, alongside the notion of stereotype, that of “pornotype”, defined as a trait resulting from the fragmentation of the sex scene and its participants in a catchy and metonymic form. We then observe that these pornotypes, in association with the thumbnail captions, do not lead to development of a story and appear as “pornographic language”. The analysis of pornographic categorisations tempts us to continue reflecting upon an interpellation process involving fiction, or, on the contrary, a production of pseudo-reality.